Ex Vivo Engineering of the Tumor Microenvironment - Aref, Amir R.; Barbie, David (Cancer Drug Discovery and Development, 2017)
This volume will outline how to recreate the tumor microenvironment, to culture primary tumors without the need for developmental priming factors, and to deliver targeted therapeutics in a manner that recapitulates pharmacokinetics in vivo. Much of what may be learned from this volume will aid in understanding many aspects of the enhanced study of tumor cell biology in a physiologic context, open new avenues for drug screening and biomarker development, and accelerate the preclinical evaluation of novel personalized medicine strategies for patients in real time.